Variations of Renal Vasculature in Multi Detector Computed Tomography Evaluation of Abdomen - Paudel, Nabin; Jha, Amit; Dahal, Ujjwal (Journal of Nepalgunj Medical College, 2022)
Introduction: Normal vascular supply to each kidney is by a single artery and vein on each side. This normal pattern is not found in all cases. Arterial variations can be accessory renal arteries which can be hilar, upper polar or lower polar and early branching. Venous variations can be late confluence, multiple renal veins and on left there can be retroaortic or circumaortic course of the left renal vein. Aims: To evaluate renal vasculature variations in patients who undergo contrast enhanced MultiDetector Computed Tomography of the abdomen. Methods: This was a hospital based cross sectional study done in 290 consecutive patients who underwent contrast enhanced Multi Detector Computed Tomography abdomen in Nepalgunj Medical College. Normal as well as variations in renal vasculature was evaluated. Results: Total of 158 (54.48%) cases had normal arterial supply. Out of 132 cases with renal arterial variation, 96 cases (72.7%) were unilateral and early branching was the most common unilateral renal arterial variation (36.4%) followed by upper polar (20.8%), lower polar (20.8%) and hilar (16.6%) arteries. Concurrent upper and lower polar arteries and combined early branching and lower polar arterial system were the most common multiple unilateral renal arterial variation seen in 2.08% cases respectively. 36 (27.27%) cases had bilateral renal arterial variations. Most cases had early branching in bilateral renal arteries seen in 9.09% cases. Venous variations were seen in 11.03%.Late confluence was the most common variation seen in 62.5% cases with variations. Rest were multiple renal veins. Left sided retroaortic and circumaortic course and bilateral renal vein variations were not found in our study. Conclusion: Renal vasculature variations were frequently observed in routine contrast enhanced Multi Detector Computed Tomography evaluation of abdomen. Renal arterial variation was more common than venous variations. Unilateral variations were more common than bilateral.